Devozione religiosa ed esperienza artistica - Lorenzetti, Tiziana (Studi e materiali di storia delle religioni, 2014)
The religious devotion, known as bhakti, arose relatively late in the religious panorama of ancient India, dominated up to then by the Vedic- Brahmanic tradition. The first part of this essay outlines the origins and the history of the so called "bhakti movement", which significantly altered the history of Indian thought. The second part analyses, in the area of Rajasthan, the cult of Śrīnāthjī, a peculiar aspect of the god Ka, who, more than other divinities, has inspired the great Hindu devotional traditions over centuries. The critical study of the multiple and complex levels of the religio-philosophical meanings associated with the cult of Śrīnāthjī and the related "path of grace" (pui mārg), is completed with a detailed analysis of some valuable paintings connected with the cult of this deity. These paintings, known as pichhwāis, belonging to the collection of the "Textiles and Arts of People of India" (tapi), were exhibited in the National Museum of History of Art of New Delhi between December 2007 and January 2008. (English)